Explaining Psychological Theories and Constructs Affecting Problematic Social Media Use in Turkish University Students from a Motivational Perspective - Kıylıoğlu, Levent (Addicta: The Turkish Journal on Addictions, 2025)
One of the most prominent behaviors among online activities performed on smartphones is social media use. In this study, problematic social media use of Turkish university students was explained from a motivational perspective by utilizing self-determination theory, uses and gratifications theory, and belongingness theories. Data were collected from 349 Turkish university students aged 18 and over. WhatsApp, YouTube, and Instagram are very popular among Turkish university students, with more than 90% of students using these platforms in their daily lives. When the relationship between the main variables used in the study is examined, it is seen that the strongest connection of Social Media Addiction Scale is with personal fear of missing out (r = 0.62, p < .01). Time spent on social media is also moderately and significantly related with Social Media Addiction Scale (r = 0.46, p < .01). Another variable with a moderately significant relationship with the Social Media Addiction Scale is entertainment (r = 0.41, p < .01). Social media usage time, personal fear of missing out, and entertainment motivations together significantly explained 46% of the variance in the Social Media Addiction Scale, with personal fear of missing out making the largest contribution to this prediction (β = .45, p < .001).